Blended Learning as a Catalyst: A Mixed-Method Study on Its Influence on Student Engagement and English Comprehension in a Batam Vocational School - Hussien, M. Rabiddin; Samanhudi, Udi; Bachtiar, Bachtiar (Journal of English Language and Education, 2025)
Blended learning, integrating traditional face-to-face instruction with online components, is increasingly recognized for its potential to transform English Language Teaching (ELT) by offering flexibility and enhancing engagement. This study aimed to investigate the impact of blended learning on students' engagement and English reading comprehension within a vocational high school in Batam. Employing a mixed-methods sequential explanatory design, quantitative data from pre-tests, post-tests, and questionnaires were collected from 80 second-grade students, supplemented by qualitative insights from semi-structured interviews with six students. Results indicated that blended learning significantly improved students' English reading comprehension, with the experimental group showing a substantial increase in scores compared to the control group. Student engagement levels were generally moderate to high, particularly in behavioural and technological aspects (students’ comfort and interaction with the digital platform and tools used for learning, including their ease of use and the perceived effectiveness of online materials), though emotional and cognitive engagement variations were observed. Qualitative findings elucidated these nuances, revealing how confidence and preference for direct instruction influenced engagement. The study underscores blended learning's robust potential to enhance academic achievement and engagement, even with mixed engagement profiles. These findings provide strong empirical evidence for integrating well-structured blended learning in vocational ELT, bridging classroom learning with workplace demands and preparing students for global career challenges.